Lack of NHE6 and Inhibition of NKCC1 Associated With Increased Permeability in Blood Labyrinth Barrier-Derived Endothelial Cell Layer - Sekulic-Jablanovic, Marijana; Paproth, Jessica; Sgambato, Cinzia; Albano, Giuseppe; Fuster, Daniel G.; Bodmer, Daniel; Petkovic, Vesna (Frontiers in Cellular Neuroscience, 2022)
Acoustic trauma, autoimmune inner ear disease, and presbycusis feature loss of the integrity of the blood-labyrinth barrier (BLB). Normal BLB function depends on endothelial structural integrity, which is supported and maintained by tight junctions and adherens junctions within the microvascular endothelial layer. When these junctions are disrupted, vascular leakage occurs. Tight junctions and adherens junctions are functionally and structurally linked, but the exact signaling pathways underlying their interaction remain unknown. In addition, solute carriers (SC) are essential for optimal exchange through BLB. Previously, we found that SC family member, the sodium–hydrogen exchanger NHE6, was expressed in all wildtype cochlear tissues, and that Nhe6 knockout mice displayed moderate hearing loss. Moreover, NHE6 depletion affected Trk protein turnover and endosomal signaling. Here, we investigated whether NHE6 might impact BLB integrity. We found that Nhe6-knockout, BLB-derived endothelial cells showed reduced expression of major junctional genes: Tjp1, F11r, Ocln, Cdh5, and Cldn5. Co-culturing BLB-derived endothelial cells with pericytes and/or perivascular resident macrophage-like melanocytes in a transwell system showed that monolayers of Nhe6-knockout BLB-derived cells had lower electrical resistance and higher permeability, compared to wildtype endothelial monolayers. Additionally, another SC, NKCC1, which was previously linked to congenital deafness, was downregulated in our Nhe6-knockout mouse model. Blocking NKCC1 with a NKCC1-specific inhibitor, bumetanide, in wildtype BLB-derived endothelial cells also caused the downregulation of major junctional proteins, particularly Tjp1 and F11r, which encode the zonula occludens and junctional adhesion molecule-1 proteins, respectively. Moreover, bumetanide treatment increased cell permeability. In conclusion, we showed that the lack or inhibition of NHE6 or NKCC1 affected the permeability of endothelial BLB-derived cells. These findings suggested that NHE6 and NKCC1 could serve as potential targets for modifying BLB permeability to facilitate drug delivery across the BLB to the cochlea or to protect the cochlea from ototoxic insults.